Determinants of engaging in business combinations through partial acquisitions - Lopes, A.; Lourenço, I. (Revista Española de Financiación y Contabilidad - Spanish Journal of Finance and Accounting, 2014)
This study investigates the firm-level and country-level conditions affecting the company’s decision to engage in partial acquisitions. For the purpose of our empirical analysis, that decision is measured thought the existence or not of Non-Controlling Interests in fourteen European countries. We find that size, leverage, profitability, cross listing, internationalization, and institutional characteristics play an important role in explaining the likelihood of engaging in partial acquisition of subsidiaries that results in reporting Non-Controlling Interests in consolidated financial statements. The main results hold, even if we replace institutional characteristics for different investor protection and securities regulation attributes. Our findings indicate that company’s incentives to engage in partial acquisitions and report NCI include the ability to access alternative sources of financing (even cross border), the ability to share risks and to obtain benefits from synergies, and the ability to enter in new markets. Our findings also enhance the importance of controlling for firm and country characteristics when doing empirical research related with NCI.